Perkembangan Teknologi Sistem Penilaian Akurasi Tendangan dalam Cabang Olahraga Taekwondo Menggunakan Teknologi Protector Scoring System (PSS): Perkembangan Teknologi Cabang Olahraga Taekwondo - Dr. Rivan Sagitha Pratama S.Pd., M.Or.; Indra Ramadhan M. Pd; Jazillah Annahdiah ADIB; Luqman Nur Fatih (STKIP Subang, 2025)
Protector scoring system (PSS) was created to help judges in the sport of taekwondo. Kicks in taekwondo are movements or techniques that are very often used in taekwondo matches because they have a high chance of producing points. The purpose of this research is to analyze the effectiveness of kick accuracy in obtaining points using the protector scoring system (PSS). The method used in this research is literature review. Researchers reviewed 15 articles from journals indexed by Sinta and Scopus. These 15 articles were analyzed based on the relevance of the articles to the problems that occurred. This research concludes that in the PSS taekwondo scoring system, points are earned through kicks that hit sensor areas on the feet (back and soles), body, and head (top of the helmet). Athletes need to understand the location of the sensors and the criteria for point validity according to the referee, and reduce ineffective movements to achieve victory. These findings encourage further research into PSS and the effectiveness of kicking techniques in scoring points.